2006
DOI: 10.1021/bi060159+
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic μO-Conotoxin MrVIB Blocks TTX-Resistant Sodium Channel NaV1.8 and Has a Long-Lasting Analgesic Activity

Abstract: MuO-conotoxin MrVIB is a blocker of voltage-gated sodium channels, including TTX-sensitive and -resistant subtypes. A comprehensive characterization of this peptide has been hampered by the lack of sufficient synthetic material. Here, we describe the successful chemical synthesis and oxidative folding of MrVIB that has made an investigation of the pharmacological properties and therapeutic potential of the peptide feasible. We show for the first time that synthetic MrVIB blocks rat NaV1.8 sodium channels and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 33 publications
(36 reference statements)
0
62
0
1
Order By: Relevance
“…Na V 1.8 has been shown to play a role in increasing excitability of nociceptors in chronic nerve injury models of neuropathic pain (Gold et al 2003;Roza et al 2003;Thakor et al 2009). In addition, A803 and another Na V 1.8 blocker, O-conotoxin MrVIB, produce analgesia in animal models of neuropathic and inflammatory pain when systemically applied, which supports a role for Na V 1.8 in contributing to chronic pain (Bulaj et al 2006;Ekberg et al 2006;Jarvis et al 2007). Further support comes from analgesic effects produced by knockdown of Na V 1.8 with antisense RNA in animal models of neuropathic pain (Joshi et al 2006;Ruangsri et al 2011).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Na V 1.8 has been shown to play a role in increasing excitability of nociceptors in chronic nerve injury models of neuropathic pain (Gold et al 2003;Roza et al 2003;Thakor et al 2009). In addition, A803 and another Na V 1.8 blocker, O-conotoxin MrVIB, produce analgesia in animal models of neuropathic and inflammatory pain when systemically applied, which supports a role for Na V 1.8 in contributing to chronic pain (Bulaj et al 2006;Ekberg et al 2006;Jarvis et al 2007). Further support comes from analgesic effects produced by knockdown of Na V 1.8 with antisense RNA in animal models of neuropathic pain (Joshi et al 2006;Ruangsri et al 2011).…”
Section: Discussionmentioning
confidence: 71%
“…TTX-R Na V 1.8 channels are expressed in DRG neurons (Bulaj et al 2006;Jarvis et al 2007), and we hypothesized that a large fraction of the Na V current in our TTX-R muscle afferent neurons was generated by Na V 1.8 channel activity. This hypothesis was supported by the slower activation and inactivation kinetics of the Na V current in TTX-R versus TTX-S neurons (Abdulla and Smith 2002;Blair and Bean 2002).…”
Section: Resultsmentioning
confidence: 87%
“…Despite the relatively few peptides identified in this class, O-conotoxins MrVIA and MrVIB have received considerable attention, because their analgesic effects in animal models of pain were ascribed to their relative selectivity for Na v 1.8 over other TTXsensitive Na v subtypes expressed in DRG neurons (Daly et al, 2004;Bulaj et al, 2006;Ekberg et al, 2006). Significant differences in their affinity at native Na v 1.8 expressed in DRG neurons and heterologously expressed Na v 1.8 have been reported.…”
Section: B O-conotoxin Inhibitors Of Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…In these studies MrVIB delivered intrathecally was analgesic at doses that produced no local anaesthetic-like inhibitory effects on movement or coordination (Ekberg et al 2006). In a separate study, synthetic MrVIB was again found to be analgesic when delivered subcutaneously to rats (Bulaj et al 2006). The solution structure of MrVIB, which includes several well defined loops and a large and apparently flexible loop II ), provides the first insights into the structural features contributing to this selective block The three-dimensional NMR structure of selected μ-conotoxins.…”
Section: O-conotoxinsmentioning
confidence: 94%